2024
DOI: 10.1001/jamanetworkopen.2023.50897
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Depression and Risk of Suicidal Behavior

Hang Yu,
Qing Shen,
Emma Bränn
et al.

Abstract: ImportanceSuicidal ideation is common among women with perinatal depression (PND). However, prospective data are limited on the risk, particularly long-term risk, of suicidal behavior (suicide attempt and completed suicide) among women with perinatal depression.ObjectiveTo examine the association between PND and risk of short- and long-term suicidal behavior.Design, Setting, and ParticipantsA nationwide population-matched cohort study was conducted in Sweden including 86 551 women with PND from 2001 to 2017 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…For example, both were more likely than their comparison groups to experience mental health–related circumstances, such as depressed mood, substance abuse (perinatal), depression diagnosis, and current mental illness treatment or past mental illness treatment (post partum). In prior research, investigators found that mental health–related circumstances increased the risk of suicide or self-harm among perinatal individuals . Within this context, our study highlights the importance of perinatal mental health screening, including for suicidal ideation, and clinical follow-up …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…For example, both were more likely than their comparison groups to experience mental health–related circumstances, such as depressed mood, substance abuse (perinatal), depression diagnosis, and current mental illness treatment or past mental illness treatment (post partum). In prior research, investigators found that mental health–related circumstances increased the risk of suicide or self-harm among perinatal individuals . Within this context, our study highlights the importance of perinatal mental health screening, including for suicidal ideation, and clinical follow-up …”
Section: Discussionsupporting
confidence: 56%
“…Previous studies that have examined quantitative factors associated with pregnancy-related deaths 8 , 9 , 10 , 11 have reported that mental health problems, substance use disorders, and intimate partner problems (IPPs) preceded suicide and homicide in pregnancy. Limitations of the aforementioned studies include sole use of older quantitative data sources, which typically reflect a limited number of states, smaller sample sizes, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous studies,67 we found that suicide mortality, although rare, yielded the highest risk elevations. Emerging data have also shown that women with PND are at increased risk of suicide attempt 36. Previous studies have often investigated deaths due to unnatural causes as a combined category, including accidents, suicides, and homicides, most likely due to small sample size 678.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data have also shown that women with PND are at increased risk of suicide attempt. 36 Previous studies have often investigated deaths due to unnatural causes as a combined category, including accidents, suicides, and homicides, most likely due to small sample size. 6 7 8 Our data are the first, to our knowledge, to show that women with perinatal depression were at an increased risk of death due to accidents alone.…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum depression (PPD) is common, affecting approximately 15% of recently pregnant individuals, and represents a major contributor to both morbidity and mortality following pregnancy. [1][2][3][4][5][6] It is associated with an increased risk for suicide and self-harm and is estimated to be responsible for 10% or more of all pregnancy-related deaths. [7][8][9] Compared to other causes of pregnancy-related deaths, those due to mental health conditions are considered preventable by many Maternal Mortality Review Committees.…”
Section: Introductionmentioning
confidence: 99%